Collaborative Governance for Waste Management in Maintaining Public Order in Kudus Regency Central Java Province - Destia Monika Pramesti; Maris Gunawan Rukmana (Institut Pemerintahan Dalam Negeri, 2025)
Waste management has become a critical issue in Kudus Regency, Central Java, particularly due to the overcapacity at the Tanjungrejo Final Disposal Site (TPA), which negatively impacts public order and environmental quality. This study aims to analyze the implementation of collaborative governance in waste management in Kudus Regency. The analysis is based on the Collaborative Governance Theory by Ansell and Gash, which includes key elements such as starting conditions, institutional design, facilitative leadership, and the collaborative process. Qualitative Descriptive Method Case Study of Governance in Waste Management in Kudus Regency, the private sector (PT. Djarum), and the community through initives such as waste banks and public seducation programs. Additionally, the Penta Helix Theory is employed as a complementary framework, involvingfive key actors: government, academia, business, community, and media. The author conduced an analysis of both theories by identifying the aligment between theoretical elements and empirical confitions in the field usding triangulations techniques. The results show that the implementation of collaborative governance in waste management has not yet been fully effective. This is evidenced by ongoing public protests and widespread illegal dumping. These issues reflect weakness in stakeholder coordinastion and a low level of public awareness regartding the importance of proper waste sorting and sustainable waste management.